Validity and reliability of a standalone low-end 50-Hz GNSS receiver during running - Padulo, Johnny; Iuliano, Enzo; Brisola, Gabriel [UNESP]; Iacono, Antonio Dello; Zagatto, Alessandro M. [UNESP]; Lupo, Corrado; Fuglsang, Thomas; Ardigò, Luca P.; Cular, Drazen (Termedia Sp. z.o.o., 2019)
The aim of the investigation was to verify the validity and reliability of a low-end 50-Hz Global Navigation Satellite System receiver (GNSSr) for different soccer-specific run distances and average speed assessments. Six soccer players were assessed on two different days while performing eight different running paths with changes of direction for a final total of 44 runs. During the runs, each participant was equipped with the GNSSr, while the time for each single run was recorded using a photocell gate. Reference vs. receiver assessment correspondences for distance and average speed were evaluated by calculating the standard error of the estimate (SEE), coefficient of variation (CV), and mean bias. Residual vs. predicted value comparison was performed by means of Bland-Altman plots. Finally, calculating the intra-class correlations coefficient (ICC) assessed the test-retest reliability of the measurement. Receiver distance assessment showed an SEE of 0.52 m (0.73%), and mean bias of 0.06 m. Receiver average speed assessment showed an SEE of 0.02 m·s -1 (0.74%) and mean bias of 0.001 m·s -1 . The Bland-Altman plot showed a small difference between the two assessments with the 95% limits of agreement=±1.08 m/0.046 m·s -1 . Receiver distance/speed assessment was found to be reliable, with ICC=0.999. In spite of its low cost, the new low-end GNSSr provides valid and reliable assessments of distance and average speed for young adults performing several standardized running actions of differing lengths within delimited setup spaces.
Keywords: Assessment Team sport Running performance Sport technology Wearable device